A novel electrochemical sensor of 4-nonylphenol based on a poly(ionic liquid) hollow nanosphere/gold nanoparticle composite modified glassy carbon electrode. Issue 19 (7th October 2015) - Ren, Jie; Gu, Jinfen; Tao, Li; Yao, Mengqi; Yang, Xiaoci; Yang, Wu
<x xml:space="preserve">Abstract</x> A well-packed film of AuNP/PIL was formed on the GCE surface.